2007
DOI: 10.1136/pgmj.2006.050260
|View full text |Cite
|
Sign up to set email alerts
|

An audit of “do not attempt resuscitation” decisions in two district general hospitals: do current guidelines need changing?

Abstract: Introduction: Doctors in all specialties are involved in making ''do not attempt resuscitation'' (DNAR) decisions; this can be a difficult and challenging process. Guidelines exist to provide an ethical and legal framework for the process and documentation of these decisions. Objective: To audit the documentation of resuscitation decisions in a sample of medical inpatients from two district general hospitals. Method: A retrospective case note audit of 50 medical inpatients, in which a DNAR decision had been ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This discrepancy between residents’ thresholds and the Ethics Council's threshold for allowing a decision, either CPR or DNAR, without patient involvement, was also found in previous studies,36 37 including in Switzerland,13 and can be interpreted in several ways. First, residents may be rationalising situations when their true reason for not including patients is the anticipation of an emotionally difficult discussion.…”
Section: Discussionsupporting
confidence: 61%
“…This discrepancy between residents’ thresholds and the Ethics Council's threshold for allowing a decision, either CPR or DNAR, without patient involvement, was also found in previous studies,36 37 including in Switzerland,13 and can be interpreted in several ways. First, residents may be rationalising situations when their true reason for not including patients is the anticipation of an emotionally difficult discussion.…”
Section: Discussionsupporting
confidence: 61%
“…Where patients’ or families’ views were sought to inform decisions about CPR, doctors sometimes felt uncomfortable ignoring their wishes and this appeared to be associated with a reluctance to discuss CPR more openly. A number of studies have found that discussions rarely take place with patients and their families12 36 37 38 and doctors often feel uncomfortable initiating such discussions 20 21 22 23. Our findings illustrate that some doctors may feel in some way obliged to follow patients’ wishes, where known, to provide CPR where they feel it would be ineffective.…”
Section: Discussionmentioning
confidence: 68%
“…A point of contention from this guidance relates to patient involvement in resuscitation decisions. Studies repeatedly find that doctors are less likely to involve patients(5–8), although they frequently discuss these decisions with relatives(2,8,9). Reasons for this paradox include feeling uncomfortable with end‐of‐life discussions(1,8), fear that it may cause undue distress to the patient or be inappropriate at that time (6) or take away hope.…”
Section: Introductionmentioning
confidence: 99%
“…A point of contention from this guidance relates to patient involvement in resuscitation decisions. Studies repeatedly find that doctors are less likely to involve patients (5)(6)(7)(8), although they frequently discuss these decisions with relatives (2,8,9). Reasons for this paradox include feeling uncomfortable with S U M M A R Y Background: 'Do Not Attempt Cardiopulmonary Resuscitation' (DNACPR) orders are made frequently for older people in hospital.…”
Section: Introductionmentioning
confidence: 99%